PENGARUH CARA BELAJAR SISWA TERHADAP KEMAMPUAN MEMECAHKAN MASALAH MATEMATIKA SISWA KELAS 5 DI SDN SRONDOL WETAN 05 SEMARANG - Ajeng Epilla Santi Nova (Jurnal Pesona Dasar, 2018)
The Effect of Student's Learning Method on Ability to Solve Mathematics Problem of 5th Grade Students at SDN Srondol Wetan 05 Semarang". Essay. Teacher Education Study Program Elementary School Faculty of Education Science University PGRI Semarang. The backgrounds that encourage this research are 1) Lack of student attention towards teachers, students themselves in learning. 2) Lack of students' ability to solve mathematical problems. 3) Lack of interest in learning, students look bored and saturated during learning because learning only uses lecture methods. The problem formulated in this research is Does the influence of student's learning on the ability to solve the problem of building the 5th grade student room of SDN Srondol Wetan 05 Semarang? Objectives to be achieved in this study to determine the effect of student learning on the ability to solve the problems of mathematics students of grade 5 SDN Srondol Wetan 05 Semarang. This type of research is ex post facto research. The research population is 30 students of grade 5 SDN Srondol Wetan 05 Semarang. The data in this research is obtained through observation, documentation, and test. Based on the final analysis that has been done visible from the results of research conducted by current researchers of 30 students classified 12 students visual way of learning, 11 students how to learn auditorial, 7 students kinesthetic way of learning. This is in accordance with the results of a survey by researchers that there are 40% of visual people, 37% of people audiovisual, 23% kinestetik people. The magnitude of the influence of independent variables on the dependent variable obtained coefficient of determination of 0.483 which means the ability to solve mathematical problems explained by way of learning by 48.3%. In addition, the researchers conducted the F-test produced below the average difference between the three ways of learning and the last research to do further test with t-test resulted that between kinesthetic and visual learning methods there are significantly, between kinesthetic and auditorial learning methods existed significant, while between the way the visual and auditorial learning differ significantly. That a different way of learning is a kinesthetic way of learning. Suggestions that writers can convey the author is that students can often practice to solve problems solving mathematical problems, so for students to be a normal thing is no longer a difficult thing.